Alteration of tumor associated neutrophils by PIK3CA expression in endometrial carcinoma from TCGA data - Yinglian Pan; Li Ping Jia; Yuzhu Liu; Yixu Han; Qingchun Deng (BMC, 2019)
Abstract Uterine corpus endometrial carcinoma (UCEC) is one of the most common cancer in female worldwide. PIK3CA has been proven to be a strong prognostic biomarker in UCEC. Nevertheless, current studies have not investigated what effects PIK3CA had on tumor associated neutrophils (TANss). Kaplan-Meier methods were used to compute the survival time of TCGA UCEC patients. GO and KEGG enrichment analysis unveiled relevant pathways PIK3CA affected using DEGs between PIK3CA high expression group and PIK3CA low expression group in TCGA UCEC, as well as GSEA. immune infiltration status was calculated using TIMER. We found that PIK3CA influenced a number of pathways including immune related pathways. The fraction of TANs was certainly altered by PIK3CA expression in UCEC. Our findings suggest that PIK3CA expression may play an important role in tumor immune microenvironment and could alter fraction of TANs in UCEC.